2021
DOI: 10.3389/fmicb.2021.625705
|View full text |Cite
|
Sign up to set email alerts
|

Mfd Affects Global Transcription and the Physiology of Stressed Bacillus subtilis Cells

Abstract: For several decades, Mfd has been studied as the bacterial transcription-coupled repair factor. However, recent observations indicate that this factor influences cell functions beyond DNA repair. Our lab recently described a role for Mfd in disulfide stress that was independent of its function in nucleotide excision repair and base excision repair. Because reports showed that Mfd influenced transcription of single genes, we investigated the global differences in transcription in wild-type and mfd mutant growth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…In these and other cases (91), Mfd was found to enhance suppression, as "without Mfd to release the polymerase, the RNA polymerase will in some instances eventually overcome the roadblock as the repressor protein dissociates" (90, p. 7). Regarding overall transcription, genome-wide gene expression analysis has shown that in mfd − cells, ∼1,000 genes are upregulated, and a comparable number of genes are downregulated (92). Significantly, in E. coli, chromosome immunoprecipitation (ChIP) sequencing analysis has shown a close correspondence between RNAP pause sites and Mfd-binding sites in the genome, and these sites in general are known or suspected sites of DNA secondary structures, including hairpins, high GC content, or G-quadruplexes (81).…”
Section: Effects Of Mfd On Recombination Spontaneous Mutagenesis and ...mentioning
confidence: 99%
“…In these and other cases (91), Mfd was found to enhance suppression, as "without Mfd to release the polymerase, the RNA polymerase will in some instances eventually overcome the roadblock as the repressor protein dissociates" (90, p. 7). Regarding overall transcription, genome-wide gene expression analysis has shown that in mfd − cells, ∼1,000 genes are upregulated, and a comparable number of genes are downregulated (92). Significantly, in E. coli, chromosome immunoprecipitation (ChIP) sequencing analysis has shown a close correspondence between RNAP pause sites and Mfd-binding sites in the genome, and these sites in general are known or suspected sites of DNA secondary structures, including hairpins, high GC content, or G-quadruplexes (81).…”
Section: Effects Of Mfd On Recombination Spontaneous Mutagenesis and ...mentioning
confidence: 99%
“…As shown in this work, these processes can be subjected to regulation with Mfd ( Figure 2 ), a transcription factor commonly associated with the repair of bulky DNA lesions in bacteria [ 81 ]. However, recent evidence has revealed that Mfd functions as a global regulator of gene transcription and cell differentiation in B. subtilis [ 34 , 82 ]. Therefore, elucidating the Mfd-dependent mechanisms that cells employ to directly or indirectly regulate the expression of the factors associated with the HPM and HPHR phenotypes will contribute to understanding the novel aspects of bacterial physiology in stressed bacterial cells.…”
Section: Discussionmentioning
confidence: 99%